Principles and estimation methods development of ecological risks initiation of emergency situations at railway transport - Zelenko, Yu. V.; Leshchynska, A. L.; Boichenko, S. V. (Science and Transport Progress, 2010)
The basic aspects of forming of ecological risks in the conditions of ecologization of transport processes are considered. The methods of probabilities estimation and management principles of ecological risks on a railway transport are offered.